Comparative patient organ dose levels for maxillofacial examinations performed with different radiological facilities. (September 2016) - Sans-Merce, Marta; Damet, Jérôme; Becker, Minerva
Abstract : Introduction: Maxillofacial radiologic examinations often result in irradiation of the thyroid gland, parotid glands and lens due to primary exposure or scatter radiation. Organ exposure depends on imaging modalities and protocols. Purpose: The purpose of this investigation was to evaluate radiation doses to the above-mentioned organs for CT, cone beam CT (CBCT) and panoramic radiographs (orthopantomography, OPT). Materials and methods: The absorbed dose was measured on the surface of a head phantom with thermoluminescence dosimeters. The phantom was imaged with CT, CBCT and OPT using standardized protocols employed in clinical routine. The areas examined included the paranasal sinuses, the entire head and the mandible depending on the protocol used. Dose measurements were performed individually for each modality and each protocol. Results: Doses to the thyroid gland when located outside the area of interest were lowest for all modalities (range: 0.01–1.22 mGy; measurement uncertainty: 10% at k = 2). Depending on the examination protocol, doses to the eye lens (due to primary beam or scattered radiation) showed wide variability (range: 0.02–26.22 mGy). The parotid glands were the only organs systematically placed in the primary beam for all modalities and protocols. Values ranged from 1.40–29.11 mGy with the highest values for CT examinations. For OPT, doses to the parotid glands were strongly inhomogeneous due to its operating mode. Conclusion: CT was the most irradiating modality. The mean doses to the parotid glands were similar for CBCT and OPT, while doses to organs in the scattered field were systematically higher for CBCT than OPT. Disclosure: The authors declare that they have no relevant material or financial interests that relate to the research described in this study.